Profit Maximization Using Simplex Method on ABC Home Industry - Yekti Condro Winursito; Munirotul Aina Bin Nur Hidayah; Widya Amelia Krisnanda; Erwan Adi Saputro (Nusantara Science and Technology Proceedings, 2022)
The home industry ABC daily produces cassava, yams, and tempeh chips. From preliminary observations, information is obtained that enables determining the composition of the number of units for each type of chip produced and determining the selling price of the product per unit, which is carried out based on experience while running the business. Therefore, there is no ideal way to define it. This condition requires a review of the company's profit to determine whether it is optimal or not. This research aims to determine the number of production units of each type of chip to obtain maximum profit and the efficiency of using cost and time resources. Data collection was carried out by observation and interviews. The mathematical model of the research problem is a linear program problem with three variables that can be solved by the simplex method. From the results of the data analysis, it was concluded that to obtain maximum profit. The company had to produce 74 units of cassava chips and 161 units of cassava chips without producing tempeh chips. The maximum profit is IDR 285.387 (previously IDR 247. 000), the production capital is IDR 889.613 (previously IDR 928.000) and all available time has been consumed.